Tweeting weight loss: A comparison of #thinspiration and #fitspiration communities on Twitter. (June 2018) - Tiggemann, Marika; Churches, Owen; Mitchell, Lewis; Brown, Zoe
Highlights: Thinspiration and fitspiration online communities were compared on Twitter. The thinspiration community is more closely connected and has greater information flow. Tweets from both forms of account focus on appearance and weight loss. Fitspiration tweets are more positive in sentiment. Abstract: Thinspiration and fitspiration represent contemporary online trends designed to inspire viewers towards the thin ideal or towards health and fitness respectively. The aim of the present study was to compare thinspiration and fitspiration communities on Twitter. A total of 3289 English-language tweets with hashtags related to thinspiration ( n = 1181) and fitspiration ( n = 2578) were collected over a two-week period. Network analysis showed minimal overlap between the communities on Twitter, with the thinspiration community more closely-connected and having greater information flow than the fitspiration community. Frequency counts and sentiment analysis showed that although the tweets from both types of accounts focused on appearance and weight loss, fitspiration tweets were significantly more positive in sentiment. It was concluded that the thinspiration tweeters, unlike the fitspiration tweeters, represent a genuine on-line community on Twitter. Such a community of support may have negative consequences for collective body image and disordered eating identity.